Explication of the contemporal concept of ensuring the security of the judiciary - Bordun, Olesia (ScienceRise: Juridical Science, 2021)
Aim. The purpose of the study was to substantiate the recommendations for the development of the concept of ensuring the security of the judiciary. Materials and methods. The study is performed based on dialectical and systematic approaches using methods of analysis, synthesis, abstraction, and generalization, as well as formal-dogmatic and structural-logical methods. The information base of the study was the scientific works of foreign and domestic scientists, the laws of Ukraine, and bylaws. Results. According to the results of the study, the hypothesis of low dynamics of development of the conceptual foundations of ensuring the security of the judiciary due to the low relevance of this issue was refuted. The hypothesis of the complexity of the development of the concept due to the interdisciplinary nature of research concerning the security of the judiciary has been confirmed. A new methodological approach is proposed, which can be used as a basis for substantiating the directions of development of conceptual bases for the formation of the organizational and legal mechanism for ensuring the security of the judiciary. Conclusions. The results of the study confirmed the dynamic nature of the concept of judicial security. Emphasis was placed on the expediency of clarifying the theoretical and methodological principles of the security of the judiciary to form a proper foundation for the continuation of judicial reform in this area. It is noted, that at the present stage the conceptual principles of ensuring the security of the judiciary are fragmented, which is explained by the interdisciplinary nature of the issue and the intersectoral nature of the legal institution. According to the results of the study, the methodological principles of substantiation of the directions of development of conceptual bases of formation of the organizational and legal mechanism of ensuring the security of the judiciary are outlined